Temperature control system / Ahmad Muzakir Ab Halim and Muhammad Firdaus Ahmad - Ab Halim, Ahmad Muzakir; Ahmad, Muhammad Firdaus (2013)
This project is temperature control system to detect heat. This project gave a cautious view on the user when the temperature reached 40 degrees Celsius, buzzer will work automatically and so the fan will switch on automatically. Function fan of this project is to produce self-trapped heat out of the room. Fan and buzzer will stop functioning when the temperature decreases below 40 degrees Celsius. The project is using the IC LM741 and IC 555. Heat detectors used in this project is the heat sensor NTC.